Women`s freestyle wrestling in global sports movement: progress analysis - Karelin, A. A.; Tarakanov, B. I.; Apoiko, R. N.; Petrov, S. I.; Koblova, V. S. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to analyze modern women`s freestyle wrestling progress trends in the context of the global sports movement history based on the statistics of the Women's World Wrestling Championships.